Effect of oral iron supplementation on functional capacity in heart failure patients: Evidence Based Case Report - Gabriela Widyakarin Tjandra; Yohanessa Wulandari (World Nutrition Journal, 2023)
Introduction: Cardiovascular disease is the leading cause of mortality worldwide. Heart failure (HF) accounts for 13.4% of deaths and reduces the quality of life of patients. Iron- deficiency is a common condition found in heart failure patients, often occurs due to decrease in iron intake, absorption, and chronic inflammation. Oral iron supplementation is a low-cost and easy alternative for iron-deficiency management in heart failure patients. Method: Literature search was conducted using advanced searching in three large databases: PubMed, Cochrane Library, and Google Scholar. MeSH terms, advanced search and eligibility criteria were used for title and abstract screening after removing duplicates. Critical assessment tools and levels of evidence of the final articles are based on the Oxford Center for Evidence-Based Medicine. Results: Two systematic reviews and meta-analyses and two RCTs met the PICO and eligibility criteria that had been set. Two systematic reviews and meta-analyses found that oral iron supplementation did not improve the functional capacity of heart failure patients, while the two RCTs found an improvement in functional capacity in heart failure patients who received oral iron supplementation. Conclusion: Based on critical reviews that have been carried out, currently we do not recommend oral iron supplementation in heart failure patients. Further research may potentially provide different recommendations as oral iron therapy evolves.